Justice environnementale dans les espaces ruraux en Afrique - Daré, William's (éditions Quae, 2023)
The notion of environmental justice is emerging in the face of evidence of differential access to environmental resources and unequal distribution of environmental risks affecting certain social groups. Often addressed in research in the North, the analysis of criteria of justice or injustice associated with the environment, such as access to water, mineral extraction or the recognition of local communities, has been little studied in Africa. However, many African territories are undergoing unbridled development to accompany their strong growth and to respond to development issues that affect the environment of the local populations. The theoretical, methodological and empirical contributions presented in this book make it possible to identify the issues of environmental justice beyond the traditional perspectives. They show how the historicity of the relations of domination between different types of actors in Africa is a determining variable in the understanding of the notion of justice. This book is intended for researchers interested in socio-environmental justice issues in the South, for NGOs fighting against these injustices, for students of social sciences and spatial planning, and for donors financing infrastructures and confronted with the growing opposition of local or international actors.